PENGARUH INVESTASI SWASTA, INDEKS PEMBANGUNAN MANUSIA (IPM), DAN BELANJA MODAL PEMERINTAH TERHADAP PDRB KABUPATEN/KOTA KALIMANTAN BARAT (2008 – 2012) - BANGUN RAJAGUKGUK, B61109051 (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT Â This study is based on the influence of private investment, both domestic and foreign investment, the Human Development Index (HDI), and the Government Capital Expenditure (BMP) to GDP of West Kalimantan. This study aims to analyze the effect of private investment made, HDI, and the Government Capital Expenditure on Economic Growth in West Kalimantan. The analytical method used was Ordinary Least Square (OLS). For purposes of analysis used secondary data in the form of cross section data, 2008 - 2012, the capital expenditures in the amount of data, domestic investment, foreign direct investment and GDP of West Kalimantan. The data obtained from the Board of Investments and Investment, BPS, and other sources that the journals and research results. Based on the estimation results together, this study found that domestic investment, foreign investment, the Human Development Index (HDI), and the Government Capital Expenditure (BMP), and a significant positive effect on GDP of West Kalimantan with determinansi coefficient (R2) of 99,78 percent. This means that the economic growth of West Kalimantan will increase with the increased investment, the Human Development Index (HDI) and the number of Government Capital Expenditure (BMP). Partially (people), the results of the analysis indicate that domestic investment, foreign investment, the amount of Government Capital Expenditure and Human Development Index (HDI) and a significant positive effect on GDP of West Kalimantan, except for Foreign Direct Investment, has a negative correlation to the direction of economic growth. Keywords: Investment (Domestic, Foreign), HDI, Government Capital Expenditure, GDP